PENERAPAN E-SYSTEM DALAM KEPATUHAN PAJAK BADAN: MODERASI PEMAHAMAN PERATURAN PERPAJAKAN DAN SANKSI PAJAK - Rhana Sasqia Hibatulwassi; Vince Ratnawati; Nita Wahyuni (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2021)
Tax is main income of Indonesia. This study aims to find empirical evidence related to the effect of taxation e-system on corporate taxpayer compliance and the effect of moderation understanding of tax regulations and tax sanctions on corporate taxpayer compliance. The population of this study is corporate taxpayers registered at Pratama Tax Office Bangkinang, amounting to 9,178 corporate taxpayers. The sample of this study was selected using accidental sampling technique, which is a sampling technique where consumers who coincidentally/incidentally meet with the researcher can be used as samples if it is deemed that the person who happened to be met is suitable as a data source. This study use approach for hypothesis testing by using SPSS 26 as statistical program used. The results of this study indicate that implementation of taxation e-system has a positive and significant effect on corporate taxpayer compliance. Meanwhile, the moderating variable such as understanding of tax regulations and tax sanctions has no effect on the implementation of taxation e-system on corporate taxpayer compliance. Keywords: taxation e-system, understanding of tax regulations, tax sanctions, taxpayer compliance